Analysis of the role of fair compensation in improving employee performance: A systematic literature review - Imam Mahfud (Priviet Social Sciences Journal, 2026)
Fair compensation has been increasingly recognized as a strategic lever for enhancing employee motivation, satisfaction, and performance in contemporary organizations. This study systematically synthesizes theoretical perspectives and empirical evidence on the role of fair compensation in improving employee performance, with particular attention to how strategic human resource management (HRM) fosters a productive and harmonious work environment. Drawing on a systematic literature review of peer-reviewed articles indexed in Scopus and Web of Science (WoS) between 2014 and 2024, complemented by foundational theoretical works, this study applied predefined inclusion and exclusion criteria covering distributive, procedural, and interactional fairness, intrinsic and extrinsic motivation, and individual and team performance metrics to identify relevant studies. The synthesis demonstrates that (1) financial and non-financial compensation jointly predicts employee performance, with non-financial recognition strengthening the effect of pay-for-performance on engagement; (2) perceptions of internal and external pay equity mediate the relationship between compensation systems and discretionary effort; and (3) effective HRM bundles, integrating workforce planning, training, performance appraisal, and transparent reward design, constitute the boundary conditions for compensation to translate into sustainable performance. Although classical scholars (e.g., Rivai, 2015) emphasize direct financial compensation as the principal driver of short-term productivity, contemporary meta-analytic evidence (Cerasoli et al., 2014; Gerhart & Fang, 2014) suggests that the joint optimization of intrinsic and extrinsic rewards yields superior long-term performance outcomes. This study contributes to HRM theory by integrating equity, expectancy, two-factor, and self-determination perspectives into a coherent fairness–performance framework and offers practical guidance for designing transparent, performance-based, and contextually fair compensation systems.